Nanocompression of secondary particles of silica aerogel. (December 2018) - Gonçalves, William; Amodeo, Jonathan; Morthomas, Julien; Chantrenne, Patrice; Perez, Michel; Foray, Geneviève; Martin, Christophe L.
Abstract: The compression of highly porous silica nanospheres is investigated using molecular dynamics simulations and modeling. The ligaments network (3–6 nm) of nano-sized silica sustains the load and nanoparticles deform plastically due to highly localized shear events, at the junctions between ligaments. Dangling ligaments are more numerous as the size of the nanosphere decreases, thus impacting the mechanical response. Based on simulation results, we propose a scaling law that describes the particle size effect on the indentation force when applied to silica aerogel secondary nanoparticles under compression. Graphical Abstract: